The role of viral particle integrity in the serological assessment of foot-and-mouth disease virus vaccine-induced immunity in swine - Mansilla, Florencia Celeste (2020)
The efficacy of foot-and-mouth disease virus (FMDV) inactivated vaccines is mainly dependent on the integrity of the whole (146S) viral particles. If the intact capsids disassemble to 12S subunits, antibodies against internal-not protective epitopes, may be induced. Serological correlates with protection may be hampered if antibodies against internal epitopes are measured. Here we compared the performance of different ELISAs with the virus-neutralization test (VNT) that measures antibodies against exposed epitopes. Sera from pigs immunized with one dose of an expired commercial FMDV vaccine were used. This vaccine contained about 50% of O1/Campos and over 90% of A24/Cruzeiro strains total antigen as whole 146S particles. Specific-total antibodies were measured with the standard liquid-phase blocking ELISA (LPBE). We also developed an indirect ELISA (IE) using sucrose gradient purified 146S particles as capture antigen to titrate total antibodies, IgM, IgG1 and IgG2. A good correlation was found between VNT titers and IgG-ELISAs for A24/Cruzeiro, with the lowest correlation coefficient estimated for IgG2 titers. For O1/Campos, however, the presence of antibodies against epitopes different from those of the whole capsid, elicited by the presence of 12S particles in the vaccine, hampered the correlation between LPBE and VNT, which was improved by using purified O1/Campos 146S-particles for the liquid-phase of the LPBE. Interestingly, 146S particles but not 12S were efficiently bound to the ELISA plates, confirming the efficiency of the IE to detect antibodies against exposed epitopes. Our results indicate that any serological test assessing total antibodies or IgG1 against epitopes exposed in intact 146S-particles correlate with the levels of serum neutralizing antibodies in vaccinated pigs, and might potentially replace the VNT, upon validation. We recommend that antigen used for serological assays aimed to measure protective antibodies against FMDV should be controlled to ensure the preservation of 146S viral particles.